Students with inattention and their experiences of autonomy in learning activities: an interview study with two students and their teachers - Uthus, Marit; Løhre, Audhild (Frontiers in Psychology, 2025)
IntroductionThe purpose of this study was to explore how students diagnosed with attention deficit hyperactivity disorder (ADHD) experience autonomy in learning activities. The study was conducted within the framework of a one-year school-based intervention using an autonomy supportive learning model that included elements of adapted education, self-regulated learning, and teacher autonomy support.MethodTwo students with inattention and two teachers were interviewed about their experiences in the context of the learning model. The interviews were inductively analyzed and self-determination theory proved useful in adding meaning to the students’ experiences.ResultsAnalysis showed that in a context that supports their autonomy, the students at times experienced being able to volitionally maintain their concentration. Autonomy support allowed them to address their own needs in terms of interest, enjoyment, and the need for breaks, leading to experiences which can be interpreted as both intrinsic motivation and autonomous extrinsic motivation. Furthermore, ongoing dialogical interactions between students and teachers were highlighted as beneficial to students’ subsequent self-reflections about their needs and what they require to act autonomously in learning activities. However, the expectations of being autonomous learners were at times experienced as a challenge for the students, indicating that autonomy in learning activities that rely on self-regulation might constitute a double-edged sword for students with ADHD. A key contribution of this study lies in its novel application of self-determination theory (SDT) to understand the broader conceptualizations of motivation—particularly internal motives of students with ADHD in mainstream educational settings—responding to recent calls for research that moves beyond deficit-based perspectives. Implications include a need for teachers to increase their competency in differentiated autonomy support. Teachers’ ongoing dialogic interaction with students about their experiences, needs and interests in learning activities should also be a central part of teachers’ competency.